The banking crisis of 2007-2008, and contemporary responses - Pinto, Rodolfo Varela (2014)
Until 2006, the financial system prospered and was stable, and Basel II rules were viewed as contributing to that stability. The financial crisis of 2007-2008 forced a change in those beliefs, as imbalances spread and risks materialized, affecting banks and other financial institutions, and impairing economic growth. We discuss the causes of the financial crisis, the response measures that were applied by governments, central banks and the changes in supervision and regulation that are being prepared under Basel III, to increase the resilience of banks, and to reduce the risks of future crisis.